PERAN KEMUDAHAN AKSES LINGKUNGAN ALAM DALAM HUBUNGAN ANTARA KEDEKATAN ALAM DAN KEBAHAGIAAN HIDUP MASYARAKAT URBAN - Yogaswari, Novalda; Ninin, Retno Hanggarani; Muliadi, Rahmad (Universitas Gunadarma, 2024)
The rapid development of urbanization is distancing people from the natural environment, especially in urban areas, including Daerah Khusus Jakarta (DKJ) or Jakarta. Jakarta has been experiencing a significant decrease in green space from year to year, making it more difficult for people to access a green environment. Therefore, this study aims to see how the role of access to natural is moderating the relationship between natural relatedness and wellbeing in urban society, especially in the Jakarta region. The research participants involved 152 people aged over 18 years old with more than 1 year stay in the Jakarta area. The quantitative research was structured and hypothesis testing was carried out using the partial least squared structural equation modeling (LPS-SEM) method. The results showed that nature relatedness was significantly correlated with wellbeing (β = 0.354, t = 3.221, p < 0.05) and access to the nature was significantly correlated with wellbeing (p < 0.05). However, there was no moderating role of access to nature on the relationship between nature relatedness and wellbeing (β= 0.027, t= 0.373, p = 0.709). The differences between the results of this study and previous studies are discussed and the characteristics of the participants involved are considered.